2008
DOI: 10.4161/cc.7.14.6272
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 expression is severely reduced in human sarcoglycanopathies and dysferlinopathies

Abstract: Aquaporin-4 (AQP4) is the major water channel expressed in fast-twitch skeletal muscle fibers. AQP4 is reduced in Duchenne and Becker Muscular Dystrophies, but not in caveolinopathies, thus suggesting an interaction with dystrophin or with members of the dystrophin-glycoprotein complex (DGC) rather than a nonspecific effect due to muscle membrane damage. To establish the role of sarcoglycans in AQP4 decrease occurring in muscular dystrophy, AQP4 expression was analyzed in muscle biopsies from patients affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Lama2 encodes a protein known to interact directly with the dystrophin complex, and mutations in Lama2 lead to muscular dystrophy (8,29). Aqp4 encodes aquaporin 4, a protein noted to be reduced in multiple forms of muscular dystrophy (1,6). Also in this region is Mib1, the mammalian ortholog of Drosophila Mib2, a gene linked to muscle growth (3).…”
Section: Discussionmentioning
confidence: 99%
“…Lama2 encodes a protein known to interact directly with the dystrophin complex, and mutations in Lama2 lead to muscular dystrophy (8,29). Aqp4 encodes aquaporin 4, a protein noted to be reduced in multiple forms of muscular dystrophy (1,6). Also in this region is Mib1, the mammalian ortholog of Drosophila Mib2, a gene linked to muscle growth (3).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, aquaporin 4, a muscle-specific water channel, was shown to be associated with sarcoglycan through α1-syntrophin, an interaction validated by its severe reduction in muscles of sarcoglycanopathy patients (Ref. 32). …”
Section: Role Of Sarcoglycans In the Dystrophin–glycoprotein Complexmentioning
confidence: 99%
“…AQP4 is expressed in healthy brain and muscle tissues (39) and well known to associate with neuromyelitis optica. The AQP4 expression is also reduced in the skeletal muscle in patients with Duchenne muscular dystrophy, Fukuyama-type congenital muscular dystrophy, and sarcoglycanopathy (39)(40)(41). In the present study, the IHC analysis revealed a decrease in the AQP4 expression in both regenerating fibers and many non-necrotic fibers in patients with IMs, particularly PM.…”
Section: Discussionmentioning
confidence: 58%